Factor mimicking portfolios for climate risk - Gianluca De Nard; Robert F. Engle; Bryan T. Kelly (University of Zurich, Department of Economics, 2024)
We propose and implement a procedure to optimally hedge climate change risk. First, we construct climate risk indices through textual analysis of newspapers. Second, we present a new approach to compute factor mimicking portfolios to build climate risk hedge portfolios. The new mimicking portfolio approach is much more efficient than traditional sorting or maximum correlation approaches by taking into account new methodologies of estimating large-dimensional covariance matrices in short samples. In an extensive empirical out-of-sample performance test, we demonstrate the superior all-around performance delivering markedly higher and statistically significant alphas and betas with the climate risk indices.
Keywords: C58; G11; G18; Q54; 330; Climate change; factor model; portfolio selection; sustainable portfolio